Nurses' experience in carrying out muscle strength exercises among patients with strokes: A qualitative study - Kartika Sari; Jenny Marlindawani Purba; Kiking Ritarwan (Malahayati International Journal of Nursing and Health Science, 2024)
Background: Patients with stroke suffer various nerve and muscle issues. The weakness and paralysis of patients with stroke affect their ability to carry out their daily activities.Purpose: To explore nurses' experiences in performing strength of muscle exercise on patients with stroke at Haji Adam Malik Central General Hospital, MedanMethod: This qualitative study with a phenomenological descriptive approach employs a purposive sampling technique to choose 10 nurses who have prior experience performing the strength of muscle exercise on stroke patients. Data are collected through in-depth interviews and then evaluated using Collaizzi method.Results: The five issues identified by the thematic analysis are the nurses’ understand about the strength of muscle exercise, challenges and solutions encountered while performing the strength of muscle exercise, how strength of muscle exercise is implemented, the need to enhance the skill in performing strength of muscle, and the nurses’ emotional reaction while performing the strength of muscle exercise on the stroke patients.Conclusion: Nurses’ knowledge of muscle strength enables them to demonstrate it to stroke patients and help them find the best solution to various challenges they may encounter.Suggestion: The need to improve nurses' skills in muscle strength exercise is related to efforts to improve the quality of nursing care for stroke patients.